PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI BANDING KONSUMEN INDOMIE DAN MIE SEDAAP) - Rizan, Mohamad; Handayani, Kartika Lestari; RP, Agung Kresnamurti (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI BANDING KONSUMEN INDOMIE DAN MIE SEDAAP)Mohamad RizanFakultas Ekonomi Universitas Negeri Jakartae-mail : Mohamadrizan72@gmail.comKartika Lestari HandayaniFakultas Ekonomi Universitas Negeri Jakartae-mail : kartikalh93@gmail.comAgung Kresnamurti RPFakultas Ekonomi Universitas Negeri Jakartae-mail : ak_prabu99@yahoo.comABSTRACTThe purpose of this research are, to know the description of purchase decision, brand image and product quality of consumen of Indomie and consumen of Mie Sedaap, test empirically the influence of brand image toward purchase decision of consumen of Indomie and consumen of Mie Sedaap , test empirically the influence of product quality toward purchase decision of consumen of Indomie and consumen of Mie Sedaap, test empirically the influence of brand image and product quality toward purchase decision of consumen of Indomie and consumen of Mie Sedaap.. The hypothesis test shows, there is significant influence from brand image and product quality toward purchase decision.Keywords: brand image, product quality, purchase decision, mie instant